The use of nanocarriers in the treatment of colon cancer: a literature review - Rossato, Aline; Silveira, Larissa da Silva; Zanella, Ivana; Sagrillo, Michele Rorato (Disciplinarum Scientia | Naturais e Tecnológicas, 2019)
Colon cancer is one of the most prevalent diseases with a high morbidity and mortality rates and is considered the 4th most common cause of cancer-related death. Nanocarriers are multifunctional platforms capable of delivering therapeutic agents to a specific tissue/cell and may enhance the therapeutic effect of the drug with the combination of magnetic hyperthermia or phototherapy. From that, this study aims to review the literature on the use of nanocarriers in the treatment of colon cancer and discuss the main found results. By analyzing the researched articles, we can conclude that the nanocarriers co-charged with drugs and genes have improved antitumor effects and an excellent efficiency in the delivery of drugs to the tumor site and are promising for the treatment of colorectal cancer.